Zawartość miedzi w glebie w różnych odległościach od krawędzi jezdni drogi krajowej nr 3 w okolicach Nowego Miasteczka = Copper content in soil at different distances from road edge national roads no 3 near Nowe Miasteczko - Walczak, Barbara; Chutko, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper presents the results of the copper concentration in the soil forms approaching high-lighted the general and potentially available to plants at different distances from the edge of the roadway at the national road No. 3 in the area of Nowe Miasteczko. The results were compared with the Polish standards. The total Cu content ranged of 6-135 mg?kg-1, and Cu potentially available to plant of 5-80 mg?kg-1.
Keywords: gleby; miedź; pH; zasolenie; soils; copper; salinity